Synthesis of highly substituted alkenes by sulfur-mediated olefination of N-tosylhydrazones - Peter Conen; Roman Nickisch; Michael A. R. Meier (Communications Chemistry, 2023)
Abstract Tetraphenylethylenes (TPEs) are well-known for their aggregation-induced emission properties. The synthesis of TPE derivatives, as well as other highly substituted olefins, generally requires the use of hazardous reagents, such as metalorganic compounds, to overcome the high activation energies caused by the sterically congested double bond. Herein, we present an efficient and metal-free procedure for the synthesis of tetraarylethylenes via alkylidene-homocoupling of N-tosylhydrazones, derived from readily available benzophenones, in excellent yields. The method relies only on cheap and benign additives, i.e. elemental sulfur and potassium carbonate, and easily competes with other established procedures in terms of scope, yield and practicability. A mechanistic study revealed a diazo compound, a thioketone and a thiirane as key intermediates in the pathway of the reaction. Based on this, a modified method, which allows for selective alkylidene-cross-coupling, generating a broader scope of tri- and tetrasubstituted olefins in good yields, is showcased as well.